A CRITICAL REVIEW OF ASSESSMENT IN ENGLISH LANGUAGE TEACHING AND LEARNING AND IMPLICATIONS FOR THE VIETNAMESE CONTEXT - Nguyen, Hong-Thu Thi; Tran, Hai-Ngoc (International Journal of Psychosocial Rehabilitation, 2020)
This article provides a critical review of assessment in English language teaching and learning that contributes a significant part to quality education of students at school. Stages and processes of school-based oral English language assessment, the relationships between assessment and instruction in classrooms and the teacher decision-making in assessment are critically analysed. A number of conclusions can be drawn from the review including the important roles of assessment in English language teaching and learning to students and the step-by-step strategies and processes of school-based assessment in relation to the teacher decision-making that provide several implications for future empirical research